Recommendations for competing sexual-asexually typified generic names in Sordariomycetes (except Diaporthales, Hypocreales, and Magnaporthales) - Réblová, Martina; Miller, Andrew N; Rossman, Amy Y; Seifert, Keith A; Crous, Pedro W; Hawksworth, David L; Abdel-Wahab, Mohamed A; Cannon, Paul F; Daranagama, Dinushani A; De Beer, Z Wilhelm; Huang, Shi-Ke; Hyde, Kevin D; et al. (IMA fungus, 2016)
With the advance to one scientific name for each fungal species, the generic names in the class Sordariomycetes typified by sexual and asexual morphs are evaluated based on their type species to determine if they compete with each other for use or protection. Recommendations are made for which of the competing generic names should be used based on criteria such as priority, number of potential names changes, and frequency of use. Some recommendations for well-known genera include Arthrinium over Apiospora, Colletotrichum over Glomerella, Menispora over Zignoëlla, Microdochium over Monographella, Nigrospora over Khuskia, and Plectosphaerella over Plectosporium. All competing generic names are listed in a table of recommended names along with the required action. If priority is not accorded to sexually typified generic names after 2017, only four names would require formal protection: Chaetosphaerella over Oedemium, Diatrype over Libertella, Microdochium over Monographella, and Phaeoacremonium over Romellia and Togninia. Concerning species in the recommended genera, one replacement name (Xylaria benjaminii nom. nov.) is introduced, and the following new combinations are made: Arthrinium sinense, Chloridium caesium, C. chloroconium, C. gonytrichii, Corollospora marina, C. parvula, C. ramulosa, Juncigena fruticosae, Melanospora simplex, Seimatosporium massarina, Sporoschisma daemonoropis, S. taitense, Torpedospora mangrovei, Xylaria penicilliopsis, and X. termiticola combs. nov.
Keywords: taxonomy; Ascomycota; pleomorphic fungi; nomenclature; protected lists